Rapid Pyrolysis of Wheat Straw in a Bench-Scale Circulating Fluidized-Bed Downer Reactor - Ding, T.; Li, S.; Xie, J.; Song, W.; Yao, J.; Lin, W. (Chemical engineering & technology, 2012)
The effects of acid washing treatment on the pyrolysis product distribution and product properties were investigated in a bench‐scale circulating fluidized‐bed (CFB) downer reactor with wheat straw as feedstock. The acid treatment not only removes most of the inorganic species present in the biomass but also alters the distribution of the remaining organic constituents. It was found that the removal of the inorganic species increases the yield of liquid product and reduces char formation and gas yield. CO and CO2 are the dominant components in the gaseous product, accounting for over 90 %. The concentration of CO in the gaseous product increases after acid treatment, while the CO2 concentration decreases. The oxygen and water contents in the liquid product are decreased on acid treatment, leading to a relatively high heating value and viscosity. More volatiles can be found in the char derived from the acid‐treated wheat straw than from the raw wheat straw. This may suggest that a longer residence time is needed for pyrolysis of the acid‐treated wheat straw in order to obtain the maximal yield of volatile matter. Pyrolysis is one of the promising routes for converting biomass into energy. The downer reactor offers significant advantages over conventional fluidized‐bed reactors. The pyrolysis behavior of wheat straw is investigated in a bench‐scale circulating fluidized‐bed downer reactor to elucidate the effects of acid treatment on the pyrolysis product distribution and product properties.